1994
DOI: 10.1161/01.atv.14.6.857
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin, sex hormones, and cardiovascular risk factors in healthy women.

Abstract: The protective effect of endogenous sex hormones is commonly believed to explain the gender gap in the risk of coronary heart disease and the diminished protection in women when menopause occurs. Recent reports indicate that iron overload, due to cessation of menstrual bleeding, may be an important factor. We therefore investigated iron stores by serum ferritin measurements in healthy premenopausal (n=113) and postmenopausal (n=46) women. Ferritin levels were higher in postmenopausal than in premenopausal wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 28 publications
6
28
1
1
Order By: Relevance
“…In effect, a link was found in the present study between serum ferritin and serum cholesterol, in agreement with Berge et al's study [48] on postmenopausal women of similar age. Ramakrishnan et al [49] demonstrated that serum cholesterol concentrations were higher among subjects with the highest serum ferritin values.…”
Section: Discussionsupporting
confidence: 94%
“…In effect, a link was found in the present study between serum ferritin and serum cholesterol, in agreement with Berge et al's study [48] on postmenopausal women of similar age. Ramakrishnan et al [49] demonstrated that serum cholesterol concentrations were higher among subjects with the highest serum ferritin values.…”
Section: Discussionsupporting
confidence: 94%
“…Iron absorption is typically inversely related to iron stores, 52 and postmenopausal women generally have higher iron stores than premenopausal or perimenopausal women. 53 For example, the average serum ferritin concentration in the postmenopausal women was 65.4 ng/mL, 18 compared to 27.3 ng/ mL in our premenopausal women. Our current results from premenopausal women agree with those from the perimenopausal women, 17 but not from those of the postmenopausal 18 women, strongly supporting the hypothesis that subjects with low iron status have higher absorption than those with adequate iron status, particularly from foods with low iron bioavailability.…”
mentioning
confidence: 48%
“…These abnormalities might lead to increased adiposity. Several studies have demonstrated correlations between serum ferritin concentrations and other components of the insulin resistance syndrome (3,4,16). It has been reported that the chelation of iron is highly resistant to oxidant-mediated injury (13) and is associated with reduced iron-induced lipid peroxidation (17).…”
Section: Multiple Regression Analysismentioning
confidence: 99%